An ecosystem for user centric learning: Revolution or evolution?. (6th February 2012) - Kirkham, Tom; Wood, Stuart; Winfield, Sandra; Coolin, Kirstie; Smallwood, Angela
The SAMSON project uses technology as a catalyst to support and aid future developments in a regional learning community. This is in contrast to many ecosystem approaches that attempt a systems overhaul. The project is developing services to encourage the use of emerging standards–based technology in existing processes. These developments are forming the community and developing the ecosystem at a natural pace that aims to enhance existing processes and encourage innovation in a sustainable manner.